Mistaking bad news for good news: investor optimism and mispricing of strategic alternatives announcements - Rim, Hyun Jung; Zha Giedt, Jenny (Review of Accounting Studies, 2026)
Companies’ strategic alternatives announcements lead to negative future stock returns. First, we investigate whether this anomaly exists. We demonstrate that it is significant and pervasive across years, industries, firm size, and information environments and that it is not driven by confounding variables nor risk. We then investigate why the market misprices the announcements and find that investors appear overly optimistic about a potential merger or acquisition and do not fully incorporate the negative fundamental news conveyed by the announcement. Meanwhile, short sellers exploit the mispricing. We also evaluate market frictions as limits to arbitrage. This study’s contributions are (i) evaluating behavioral and risk explanations for an event that causes extreme stock returns, (ii) challenging investors’ widely held belief that such announcements reflect good news, and (iii) warning investors and analysts about a behavioral bias they might unknowingly adopt.